Pengembangan dan Validasi Instrumen Indentifikasi Penyesuaian Sosial Siswa Sekolah Menengah Atas - Setiana, Setiana; Taufik, Agus; Rusmana, Nandang; Nurihsan, Juntika (Universitas Muhammadiyah Metro, 2023)
Social adjustment in adolescents is a crucial process in individual development. High school adolescents often face various environmental changes and social pressures that differ from those at other ages. Reasonable social adjustment can help adolescents cope with problems and promote positive social and emotional development. However, poor adjustment can lead to mental and social health issues. This article explores various aspects of social adjustment in high school adolescents, including influencing factors, adjustment stages, and effective interventions. This study aims to develop an instrument that can be used to identify students' social adjustment. The participants involved in developing this instrument were 41 students aged 14-16 years (mean=0.80 and SD=0.83). The reliability value of the items is in the excellent category (0.918). Out of 50 statements developed, after testing validity and reliability, 49 statements are suitable for measuring students' social adjustment.